Pseudoxanthomonas helianthi sp. nov., isolated from roots of Jerusalem artichoke (Helianthus tuberosus) - Chokchai Kittiwongwattana; Chitti Thawai (My University, 2016)
A bacterium designated as strain roo10T was isolated from roots of Jerusalem artichoke (Helianthus tuberosus). Cells were Gram-stain-negative and non-motile rods. The phylogenetic analysis of the 16S rRNA gene indicated that it represented a member of the genus Pseudoxanthomonas, and its close relatives included Pseudoxanthomonas kalamensis JA40T (97.8 % 16S rRNA gene sequence similarity), Pseudoxanthomonas sangjuensis 5GH38-5T (97.7 %) and Pseudoxanthomonas daejeonensis TR6-08T (97.1 %). Growth of roo10T occurred at pH 7-9. The temperature for growth ranged from 20 to 37 °C. Tolerance to NaCl was observed from 0.005 to 5 % (w/v) concentration. Predominant fatty acids were iso-C15 : 0 (23.5 %), iso-C16 : 0 (18.9 %) and anteiso-C15 : 0 (11.5 %). Diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and phosphatidyl-N-methylethanolamine were the major polar lipids. The predominant quinone was ubiquinone 8 (Q-8). The DNA G+C content was 65.7 mol% [from melting temperature (Tm)]. Comparison of phenotypic and chemotaxonomic characteristics indicated that roo10T was distinguishable from its close relatives. Additionally, the DNA-DNA relatedness levels between roo10T and P. kalamensis DSM 18571T (22±0.5 %), P. sangjuensis 5GH38-5T (21±0.2 %) and P. daejeonensis DSM 17801T (3±1 %) were lower than 70 %. These results indicated that roo10T represented a novel species of the genus Pseudoxanthomonas, for which the name Pseudoxanthomonas helianthi sp. nov. is proposed. The type strain is roo10T (=BCC 70700T=NBRC 110414T).
Keywords: Helianthus; Jerusalem artichoke; Microbial Metabolites in Food Biotechnology